Note-Taking Method for Listening Ability of University Students - Suyadi Suyadi; Berliana Safitri; Putriani Putriani (Universitas Batanghari Jambi, 2023)
The goal of this study was to ascertain whether the note-taking method had any effect on listening comprehension during the second semester of English Language Education at the Faculty of Teacher Training and Educational Sciences of the University of Batanghari. Both the experiment class and the control class participated in the research, which was done using an experimental methodology. 30 students from two classrooms were included in the study's sample, which was conducted during the second semester. There were 15 pupils in each of the two classesâ€”the experiment class (X) and the control class (Y). The researcher used the listening test to acquire data. The two tests were the pretest and the post-test. The formula used to analyze the data was the T-test. The pretest mean for the experiment class was 58.67, whereas the post-test mean.Â